Pengaruh Program Tutor Sebaya Melalui Home Visit Terhadap Kepatuhan Berobat pada Pasien Diabetes Mellitus - Daud, Vebriyanti; Fani, Rif'atul; Nawangwulan, Tama Mega (Pustaka Galeri Mandiri, 2025)
Diabetes mellitus is a metabolic condition marked by increased blood glucose levels resulting from a gradual reduction in insulin production. This research seeks to assess the impact of a peer tutoring program conducted via home visits on medication adherence and blood glucose levels in diabetes mellitus patients in the hamlet of Bube, Suwawa district. This research used a one-group pretest-posttest pre-experimental design including 30 diabetes patients who were purposively chosen due to their prior non-adherence to treatment. Blood glucose levels were quantified using a glucometer, and patient adherence was evaluated by pre- and post-test questionnaires. Data were analyzed using the McNemar test for adherence and paired t-test for blood glucose. Results showed a significant increase in adherence, from 13 (43.3%) to 27 (90%), and a decrease in mean blood glucose from 244.03 mg/dL to 220.97 mg/dL (t = 2.77; df = 29; p < 0.05) after the intervention. These findings indicate that the peer tutor home visit program effectively improves adherence and reduces blood glucose, providing a feasible community-based strategy for diabetes management.